Associations between mild-to-moderate anaemia in pregnancy and helminth, malaria and HIV infection in Entebbe, Uganda - Muhangi, Lawrence; Woodburna, Patrick; Omara, Mildred; Omoding, Nicholas; Kizito, Dennison; Mpairwe, Harriet; Nabulime, Juliet; Ameke, Christine; Morison, Linda A.; Elliott, Alison M. (Transactions of the Royal Society of Tropical Medicine and Hygiene, 2017)
It is suggested that helminths, particularly hookworm and schistosomiasis, may be important causes of anaemia in pregnancy. We assessed the associations between mildto-moderate anaemia (haemoglobin >8.0 g/dl and HIV among 2507 otherwise healthy pregnant women at enrolment to a trial of deworming in pregnancy in Entebbe, Uganda. The prevalence of anaemia was 39.7%. The prevalence of hookworm was 44.5%, Mansonella perstans 21.3%, Schistosoma mansoni 18.3%, Strongyloides 12.3%, Trichuris 9.1%, Ascaris 2.3%, asymptomatic Plasmodium falciparum parasitaemia 10.9% and HIV 11.9%. Anaemia showed little association with the presence of any helminth, but showed a strong association with malaria (adjusted odds ratio (AOR) 3.22, 95% CI 2.43—4.26) and HIV (AOR 2.46, 95% CI 1.90—3.19). There was a weak association between anaemia and increasing hookworm infection intensity. Thus, although highly prevalent, helminths showed little association with mild-to-moderate anaemia in this population, but HIV and malaria both showed a strong association. This result may relate to relatively good nutrition and low helminth infection intensity. These findings are pertinent to estimating the disease burden of helminths and other infections in pregnancy. [Clinical Trial No. ISRCTN32849447]
Keywords: Anaemia; Helminth; Pregnancy; HIV; Malaria; Uganda